Efektivitas Farmakologi Senyawa Aktif Tumbuhan Mangrove Yang Hidup Di Indonesia - Dwi Bagus Pambudi; H Haryoto (Jurnal Ilmiah Kesehatan, 2022)
Mangroves are ecologically important plants in marine habitats that occupy the coastlines of several countries. Apart from their primary ecological importance, various parts of mangroves are widely used in traditional medicine and are claimed to be effective in treating various diseases. At present, no comprehensive effort has been made to compile and critically analyze the published literature in view of its ethnopharmacological utility. This review aims to provide a comprehensive overview of the biodiversity and distribution of mangrove plants, ethnopharmacology, phytochemical profiles, and pharmacological activities of mangrove plants used as traditional medicine in Indonesia. The method used is by using literature studies from the Science Direct, Pubmed, and Google Scholar database. Result show that In Indonesia, there are 33 types of mangrove species, all of which are traditionally used as medicine, which are spread throughout the archipelago in Indonesia. Bioactive compounds obtained from mangrove plants include polyphenols, flavonoids, alkaloids, carotenoids, tannins, saponins, steroids, amino acids, carbohydrates, proteins, vitamins etc. This review also shows that the pharmacological activities of mangrove plants in general include antimicrobials (such as antibacterial, antiviral and antifungal), anti-inflammatory, anti-ulcer, antidiarrheal, anticancer, antidiabetic, anti-HIV, antinociceptive, hepatoprotective, antiarthritis, analgesic, antioxidant and cytotoxic activities.